2023
DOI: 10.1039/d3fo01255g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coenzyme Q10 on cardiac function and survival in heart failure: an overview of systematic reviews and meta-analyses

Eva Alarcón-Vieco,
Irene Martínez-García,
Irene Sequí-Domínguez
et al.

Abstract: Heart failure (HF) is associated with a deficiency in blood levels of coenzyme Q10 (CoQ10), and its supplementation has been proposed. The aim of this systematic review was to synthesise...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…CoQ10 benefits cardiovascular health as it can help reduce total cholesterol, improve endothelial function, and fight inflammation and oxidative stress. This also makes it a suitable option for treating COVID-19 [106][107][108][109][110]. A recent meta-analysis found that CoQ10 supplements taken for 10 weeks or less at doses above 200 mg/day may lower malondialdehyde (MDA), TNF-α, and IL-6 levels.…”
Section: Coenzyme Q10 (Coq10)mentioning
confidence: 99%
“…CoQ10 benefits cardiovascular health as it can help reduce total cholesterol, improve endothelial function, and fight inflammation and oxidative stress. This also makes it a suitable option for treating COVID-19 [106][107][108][109][110]. A recent meta-analysis found that CoQ10 supplements taken for 10 weeks or less at doses above 200 mg/day may lower malondialdehyde (MDA), TNF-α, and IL-6 levels.…”
Section: Coenzyme Q10 (Coq10)mentioning
confidence: 99%
“…Therefore, for accurate contour tracking of the left ventricle, especially in high-resolution images, it is necessary to appropriately adjust the traditional GAC model to ensure that the contours can accurately capture the dynamic boundaries of the left ventricle. Assuming the gradient characteristic function on image 2 , represented by h. The main force dragging the contour to the target edge in the GAC model is represented by the term hθ, and the reconstructed GAC level set iteration equation is given by: hh s…”
Section: Lower Layer Image Processingmentioning
confidence: 99%
“…In contemporary medical diagnostics, precise assessment of cardiac function is crucial for the treatment and management of patients with heart failure. Heart failure is a severe clinical condition involving a decline in cardiac pumping capability, affecting systemic blood circulation [1][2][3]. Dynamic cardiac ultrasound imaging, a non-invasive and cost-effective diagnostic method, can visually display the cardiac motion state and is valuable for assessing left ventricular function [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is critical for cellular functions ( Hargreaves et al, 2020 ), particularly in energy production through adenosine triphosphate synthesis ( Aussel et al, 2014 ), acting as an antioxidant to combat free radicals ( Bentinger et al, 2007 ), and inhibiting lipid peroxidation to protect cell membranes from oxidative damage ( Zhang et al, 2013 ). Clinically, CoQ10 is utilized in the management of heart failure and myocarditis, owing to its ability to preserve the morphology and structure of mitochondria in ischemic cardiomyocytes ( Alarcón-Vieco et al, 2023 ). Moreover, it is also used in the treatment of antioxidants ( Samimi et al, 2024 ) and maintenance of muscle function ( Talebi et al, 2024 ).…”
Section: Impact Of Nutrients On the Ocular Surface And Potential Risksmentioning
confidence: 99%